Telepharmacy Education As A Step To Strengthen The National Health System In Pandeglang Regency: Edukasi Telefarmasi Kepada Masyarakat Kabupaten Pandeglang Sebagai Langkah Memperkuat Sistem Kesehatan Nasional - Yusransyah, Yusransyah; Stiani, Sofi Nurmay; Ismiyati, Renditya; Udin, Baha; Pratiwi, Linda Rani; Maharani, Sylvianti; US, Sumarlin; Ernawati, Eneng Elda (Universitas Lancang Kuning, 2024)
A health sector that uses information and communication technology (ICT) can offer a new perspective on health service delivery and help overcome the problem of insufficient availability of health workers. The form of implementation can be telepharmacy services, but only a few people understand telepharmacy. This service aims to provide telepharmacy education to the people of Pandeglang Regency as a first step to strengthening the National Health System. Health education is delivered through visualization using the community relations method. As part of the Community Service program, this activity aims to provide telepharmacy education to the people of Pandeglang Regency, which is part of improving the National Health System.